Kinetics and Mechanism of Oxidation of Cobalt (II) by Iron (III) in the Presence of 1,10 Phenanthroline - Bassem F. Shraydeh (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
The kinetics of oxidation of cobalt (II) by iron (III) in the presence of 1, 10 phenanthroline has been investigated spectrophotometrically. Hydrogen ions exhibited an inhibitory effect on the rate of the reaction while 1,10 phenanthroline showed an accelerating effect The order with respect to iron (III) was found to be unity. On the other hand, the order with respect to cobalt varies with its concentration being 0.3+ 0.004 at high concentration and 0.791-0.019 at low concentrations. A plausible mechanism was postulated and a rate law was derived that accounted for the various experimental results obtained.